PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN PENGGUNAAN, KEPERCAYAAN DAN PERSEPSI RISIKO TERHADAP MINAT UNTUK MENGGUNAKAN INSTRUMEN UANG ELEKTRONIK - Yogananda, Andrean Septa; Dirgantara, I Made Bayu (Diponegoro Journal of Management, 2017)
Money as payment tools has developed rapidly over time. The development of money is also affected by the development of information technology, that created electronic money. Transaction volume and transaction value of electronic money has increase recently with the increasing of customer needs on payment tools. Many factors influence the consumer's desire to use electronic money. This research’s objectives are to test the effect of perceived benefits, perceptions of ease of use, trust and perceptions of risk to interest in using electronic money instruments. Taking a sample of 120 respondents from selected enrolled student of the school year 2016/2017 from Management Department Faculty of Economics and Business Diponegoro University. This research using nonprobability sampling technique for selecting respondents. The method of data analysis used is multiple regression analysis, where the analysis consist of validity test, reliability test, classical assumption test, multiple linear regression test, t test, and F test. The result shows that perceived usefulness, perceived ease of use and trust have positive and significant effect to intention to use, while perceived risk has negative and not significant effect to intention to use.